Deceptive cognates of Visayan dialects and Tagalog - Tabujara, Ester Gonzalez 1934- ([Quezon City s.n.], 1969)
The study aims to describe the deceptive cognates of Visayan dialects and Tagalog. It aims to make a contrastive analysis of the form, meaning, and distribution of these deceptive cognates for the purpose of predicting learning problems. Through the study, the researcher hopes to bring about better understanding of the nature and quality of deceptive cognates of some Philippine dialects, among others.
Thesis (Master of Arts in Teaching English as Second Language)--University of the Philippines
Typescript
Keywords: Bisaya language; Tagalog language